A green approach to synthesis Iron nanoparticles by using Averrhoa bilimbi linn - Inas Raihani Binti Rosli (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This research study is about the synthesis of iron nanoparticles from the natural sources of Averrhoa bilimbi Linn. using different plant parts. The plant extracts act as natural reducing agent in producing iron nanoparticles. There is no addition of any surfactants during the nanoparticles formation. The gravimetric analysis is used to calculate the percentage yield of plant extracts. The highest result of percentage yield is fruit extract is 50% using maceration and 49.89% using sonication extraction compared to leaf, twig and bark extracts. The Total Phenolic Content (TPC) and DPPH free radical activity were analyzed to evaluate the antioxidant activity in different A. bilimbi extracts and iron nanoparticles. From the TPC result, the fruit extract showed highest phenolic content which is 27.26 mg GAE/g and 39.46 mg GAE/g for iron nanoparticles. Meanwhile, from the result DPPH free radical antioxidant activity, the fruit extract also showed the highest result which is 61.93% in A. bilimbi and 80.00% in iron nanoparticles. The highest efficiency of percentage yield and antioxidant activity is fruit followed by leaf, twig and bark. Next, the iron nanoparticles were analyzed by using UV-Vis Spectrophotometer and the broad peak absorbance were at 465 nm, 450 nm, 460 nm and 440 nm for iron nanoparticle that used fruit, leaf, twig and bark as reducing agent. Meanwhile, there are two peak that showed the presence of functional group in FTIR analysis which is at 3368 cm-1, 1644 cm-1, 3383 cm-1 and 1693 cm-1 which represent functional group of amine and alkene.